The Effect of on Time Performance, Tracking System and Cargo Insurance on Customer Loyalty Through Customer Satisfaction Moderated By Age - Isti Fani; Edi Abdurachman; Juliater Simarmata; Nofrisel Nofrisel (Dinasti International Journal of Education Management and Social Science, 2026)
This study examines the effects of on-time performance, tracking systems, and cargo insurance on customer loyalty in logistics services, with customer satisfaction as a mediating variable and age as a moderating factor. A quantitative approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires from 318 logistics service users, providing adequate statistical robustness. The findings indicate that on-time performance, tracking systems, and cargo insurance significantly influence both customer satisfaction and customer loyalty. Customer satisfaction plays a key mediating role by strengthening the relationship between service attributes and loyalty. Moderation analysis shows that age strengthens these relationships among Generation Z. Overall, the study highlights the critical role of service reliability, information transparency, and risk protection in enhancing customer satisfaction and loyalty in logistics services